Pengaruh Video Animasi Berbasis Animaker Terhadap Hasil Belajar Siswa di Sekolah Dasar - Sofyan Iskandar; Primanita Sholihah Rosmana; Alifia Nur Azizah H. A; Gina Selvia Rahayu; Melan Aprilianti; Popy Gustini (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Free animation video creation facilities like this actually have a pretty good opportunity, especially in the field of education to develop teaching materials in schools, but there is a lack of educator exploration in developing teaching materials, so it is still quite rare for educators to use these tools for learning needs. Even though the animated video created can become a visual learning environment that children usually like and become a magnet for children to learn. Using an Animaker-based learning environment allows for improved quality of student learning to achieve better learning outcomes. Using an Animaker-based learning environment allows for improved quality of student learning to achieve better learning outcomes. The method used is the pre-test method with a post-test one group pre-test design. This study was conducted at SD Negeri 1 Ciseureuh with a sample of 34 grade V students. The results show that the final test score is higher than the initial test score, and the average initial test score and the final test are 6 and 9, respectively. It can be concluded that the use of animaker-based videos has a positive impact with the improvement of student learning outcomes. Keywords : Animaker, Learning Media, Learning Outcomes, Elementary School